2011
DOI: 10.1371/journal.pone.0018043
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Long-Term Protection of Adult Offspring Born to High-Fat Fed Dams against Obesity Induced by a Sucrose-Rich Diet

Abstract: BackgroundMetabolic and endocrine environment during early life is crucial for metabolic imprinting. When dams were fed a high fat diet (HF diet), rat offspring developed hypothalamic leptin resistance with lean phenotype when weaned on a normal diet. Interestingly, when grown on the HF diet, they appeared to be protected against the effects of HF diet as compared to offspring of normally fed dams. The mechanisms involved in the protective effect of maternal HF diet are unclear.Methodology/Principal FindingsWe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 36 publications
(43 reference statements)
1
31
0
Order By: Relevance
“…We minimized the impact of the other factors that influence the progeny phenotype, such as genetic background (26), maternal diet (7,17), litter size, and individual maternal body conditions (38) because the dams belonged to the same line and were fed the same standard diet and because only one male and/or one female from the same mother and only from litters of six pups were studied. In addition, the use of this model allowed us to avoid the impact of stress associated with experimental manipulations (surgery, injections) on progeny development.…”
Section: Discussionmentioning
confidence: 99%
“…We minimized the impact of the other factors that influence the progeny phenotype, such as genetic background (26), maternal diet (7,17), litter size, and individual maternal body conditions (38) because the dams belonged to the same line and were fed the same standard diet and because only one male and/or one female from the same mother and only from litters of six pups were studied. In addition, the use of this model allowed us to avoid the impact of stress associated with experimental manipulations (surgery, injections) on progeny development.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, not all the studies arise to the same conclusion. There are examples in which HFD given during gestation and lactation protects, at least partially, the offspring from excessive weight gain through different hypothalamic mechanisms (Couvreur et al, 2011). So, more studies are needed to elucidate the intrinsic mechanism related with these effects, and complementary studies in humans should be envisaged.…”
Section: Hypercaloric and High-fat Dietsmentioning
confidence: 99%
“…Findings were similar according to maternal treatment, except Western-type maternal diet tended to induce weaker effects on offspring when control diets were matched for energy (White et al, 2009) or micronutrient (Zhang et al, 2013) content. In general, offspring experimental diets were applied at weaning through the end of the study period; based on the small number exceptions (Arentson-Lantz et al, 2014; Brenseke et al, 2015; Couvreur et al, 2011; Khanal et al, 2014; Llopis et al, 2014; Ong and Muhlhausler, 2014; Vido et al, 2014; Wallace et al, 2012), we observed no remarkable patterns with regard to the post-gestational timing of exposure to experimental offspring diets.…”
Section: Introductionmentioning
confidence: 77%
“…These experimental diets are high in fat, specifically saturated fat (e.g., (Ainge et al, 2011; Fan et al, 2013; Page et al, 2009; Tamashiro et al, 2009; White et al, 2009)) and in some studies, also high in sugar (e.g., (Couvreur et al, 2011; Khanal et al, 2015)). Therefore, our discussion focuses on maternal or offspring “Western diet”, defined as a diet high in saturated fats and/or sugars.…”
Section: Introductionmentioning
confidence: 99%